A study on peripartum hysterectomy in a tertiary referral government hospital - M., Chaithra; K., Tejeswini K.; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency peripartum hysterectomy (EPH) is a major surgical venture invariably performed in the setting of life-threatening haemorrhage during or immediately after abdominal and vaginal deliveries. Aim of the study was to study the frequency and indications for peripartum hysterectomy and to assess the maternal outcome of peripartum hysterectomy. Methods: Cross sectional study was done in the department of obstetrics and gynaecology, Vanivilas hospital, Bangalore from September 2018 to august 2019. This study consists of 24 cases of emergency peripartum hysterectomy within 24 hours of delivery, operated at Vanivilas hospital. Results: The frequency of peripartum hysterectomy was 1.102/1000 deliveries and following caesarean section and vaginal deliveries are 3.544/1000 deliveries and 0.248/1000 deliveries respectively. Among 24 cases who had peripartum hysterectomy, 16 cases were delivered by caesarean section and 4 cases delivered by vaginal route while another 4 cases delivered by laparotomy for rupture uterus. 22 cases (91.67%) survived with major number of cases having morbidities and there were 2 (8.33%) maternal death. Conclusions: The most common mode of delivery before peripartum hysterectomy was Caesarean section. The most common indication was atonic postpartum haemorrhage. Better protocols for induction and augmentation of labour will decrease the necessity of peripartum hysterectomies.